Optimizing the Resistivity of Colloidal SnO₂ Thin Films by Ion Implantation and Annealing - Yusuf, AS; Markwitz, M; Chen, Z; Ramezani, M; Kennedy, JV; Fiedler, H (Elsevier BV, 2024)
Tin oxide (SnO₂) is a critical material for a wide range of applications, such as in perovskite solar cells, gas sensors, as well as for photocatalysis. For these applications the transparency to visible light, high availability, cheap fabrication process and high conductivity of SnO₂ benefits its commercial deployment. In this paper, we demonstrate that the resistivity of widely colloidal SnO₂ can be reduced by noble gas ion beam modification. After low energy argon implantation with a fluence of 4×10¹⁵ at.cm⁻² at 25keV and annealing at 200°C in air, the resistivity of as-deposited film was reduced from (178±6)μΩcm to (133±5)μΩcm, a reduction of 25%. Hall effect measurements showed that the primary cause of this is the increase in carrier concentration from (8.1±0.3)×10²⁰ cm⁻³ to (9.9±0.3)×10²⁰ cm⁻³. Annealing at 200°C resulted in the removal of defect clusters introduced by implantation, while annealing at 300°C resulted in the oxidation of the films, increasing their resistivity. The concentration of oxygen vacancy defects can be controlled by a combination of low energy noble gas ion implantation and annealing, providing promising performance increases for potential applications of SnO₂ where a low resistivity is crucial.
Keywords: 40 Engineering; 4016 Materials Engineering; 34 Chemical Sciences; 3406 Physical Chemistry; 4016 Materials engineering; Tin oxide; Argon; Implantation; Annealing; Resistivity